Developmental biology - Gilbert, Scott F (Sinauer Associates, 2000)
Developmental Biology, Sixth Edition captures the richness, the intellectual excitement, and the wonder of contemporary developmental biology. It is written for junior- and senior-level undergraduates who have taken a course in either cell biology or genetics. In addition to exploring and synthesizing the organismal, cellular, and molecular aspects of animal development, the Sixth Edition expands its coverage of the medical, environmental, and evolutionary aspects of developmental biology.
Keywords: vývojová biologie; embryologie; Developmental Biology; Embryology; biologie; embryologie a teratologie